Sarawak Chinese literature in Taiwan or local Sarawak Chinese literature: A perspective from regional experience towards rainforest writing - Chai, S.L. (2016)
The concept of 'Sinophone literature' reminds us that in this new century, the ideology of literary history is no longer stringent, as a result, the geographical view of literature should be changed accordingly as well. When we agree that Sarawak Chinese literature does not belong to Mahua literature, can we then classify all Sarawak Chinese literature into one category? This is the main argument of the paper. This paper consists of three parts. The first part discusses what does the strengthening of indigenous Sarawak Chinese literature mean based on the characteristics of the island of Borneo. The second part divides Sarawakian Chinese authors in two groups, namely 'Taiwan-based authors' and 'local authors' and further examines how regional experience affects their works. It is, however, difficult to distinguish which part is affected by Taiwan's influence and which part is their self-creation, especially in this era of globalisation. In spite of that, we can narrow the scope of study down to the works of rainforest writing of Sarawakian Chinese writers to gain more refined study. Therefore, the fictional works of Li Yongping ('o/ jj( -'17 .) and Chang Kuei-hsin ('lR ~UJ~) who have been resided in Taiwan for many years will be taken as examples and compared with the works of local authors on rainforest writing, the differences and individual complexity between both will then be questioned and deliberated. Finally, the dialogues or contrasts between Sarawak Chinese literature in Taiwan and local Sarawak Chinese literature will be analysed based on the criticism and self- criticism in 'Sinophone Iterature'.